Synthesis and Identification with Biological Evaluation of Some Metal Ions Complexes Derived from Thymine-Azo Ligand - Al-mizher, Tabark Taha; Abbas, Alyaa Khider (Indonesian Journal of Chemistry, 2025)
New series of Ag(I) and Cu(II) complexes with general formulas of Ag(AAT)(H2O)]NO3·H2O and Cu(AAT)(H2O)3]Cl2·H2O from 6-((5-chloro-2-hydroxyphenyl)diazenyl)-5-methylpyrimidine-2,4(1H,3H)-dione (AAT) were synthesized. By using FTIR, UV-vis, MS, and 1H-NMR, their molecular structural and binding properties were confirmed, which indicated that the AAT ligand acts as a neutral tridentate O, N, and N, forming tetrahedral geometry with Ag-AAT and distorted octahedral with Cu-AAT. Additionally, C.H.N analysis, magnetic susceptibility, molar conductivity, and thermal analysis were used to identify the synthesized compounds' stability and molecular formula and explore their physical and chemical properties. XRD and AFM were also examined, where the ligand and Cu(II) complex exhibited nanoscale properties. The biological potential of these compounds was also investigated by testing their antioxidant activity. Furthermore, the Cu(II) complex was investigated for its effects on liver function and histological abnormalities in male albino rats. The enzymatic activities of liver markers such as glutamic-oxaloacetic transaminase, glutamic-pyruvate transaminase, and alkaline phosphatase were measured to determine the hepatoprotective properties. Histological investigations of liver tissues revealed further evidence for the biological effects of the copper compound. These results revealed the potential applications of Ag(I) and Cu(II) complexes derived from the thymine-azo ligand.